Reingeniería de procesos para la empresa Dilmecsa S.A., de la ciudad de Guayaquil - Robles Zea, Presley Segundo (2015)
This paper called "reengineering FOR NOW DILMECSA SA, CITY OF GUAYAQUIL" main objective is to establish a redesign of processes by reengineering therefore should potentiate the skills of internal customer to direct them to a highly efficient service that promotes the same loyalty in the market, which may lead to a high position thus creating a comprehensive organizational development. The specific objectives were raised are: Identify current business processes DILMECSA SA; Prioritize processes that need to be redefined; Redesign processes by drawing flowcharts for each process identified; Define those responsible for each project redesigned; Establish the impact caused implementing reengineering proposal. Within the methodology used for the development of this research work, methods, techniques and tools for data collection. The analytical method was used to perform the analysis of the information that is collected in the field work. The deductive method, this method part of the general principles and then specify particular facts or phenomena, and used in the development of the different categories, concepts and definitions used in preparing the theoretical foundation. The descriptive method, I use it in the current observation of facts, events and cases, which seeks rational interpretation and objective analysis thereof. And the statistical method, which allowed for the construction of qualitative and quantitative information collected in the investigation. Observation technique was performed for all processes and activities of the company DILMECSA SA Interview, the legal representative of the company in order to obtain information about the company was applied. And the survey, which was applied to the 120 customers and 26 employees of the company. The part concerning the results, presented a brief history of the company, the diagnosis of the current situation of the company, where it is determined that the company presents some difficulties within its structure while there are some policies and values presented is too little staff training, SWOT analysis indicate where the opportunities and threats "DILMECSA" according to a weighting, the result of high-impact matrix. In discussing the current survey and design processes is presented, establishing four macro processes that are purchases recording, registration services, hiring and job advancement control of the key processes that are purchasing is determined, service delivery, hiring, work feed control and collection process. The plan to improve arose, structuring a team, naming process leaders, to improve resulting in the reduction of 425 minutes in the purchases record 145-minute recording service delivery, 260 minutes in hiring employees and 25 minutes in the feed control work. Concerning the determination of the costs for the implementation costs are generated not because what he did is the equitable distribution of burdens and responsibilities, and a reduction is achieved in the business processes of 705 minutes. Finally, conclusions according to the goals and the recommendations made after completion of the work is established, the literature used to fully understand the issue and Annexes where the formats of surveys and interviews, together with the summary of draft.